An Analysis of Moral Value in The “Encanto” Movie by Walt Disney Studios - Ichwani, Valrayna; Nuriadi, Nuriadi; Saputra, Agus (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2026)
Movies frequently serve as a medium for educating large audiences about social, cultural, and moral issues. Through its characters and plot, Encanto, one of Disney's culturally grounded productions, offers deep ethical messages. The purpose of this study is to determine the moral principles depicted in Encanto by Walt Disney Studios and examine how they relate to Colombian society's cultural background. Using Linda and Eyre's (1993) categorization of moral values—Values of Being and Values of Giving—as the main analytical framework and Abrams' (1971) pragmatic theory to assess cultural relevance, a qualitative descriptive technique was utilized. The information was gathered using document analysis of the movie's speech and scenes. Twenty examples of moral values—honesty, courage, peaceability, self-assurance, discipline, loyalty, respect, love, selflessness, kindness, and justice—are revealed by the research. Love stands out as the most important of these. The analysis also shows that these values reflect key features of Colombian culture, including familismo, armonía familiar, and respeto a los mayores. In conclusion, Encanto is a significant medium for moral instruction and cultural principles, especially those ingrained in Colombian family life, in addition to being a source of amusement.